2020
DOI: 10.3390/plants9050589
|View full text |Cite
|
Sign up to set email alerts
|

Is the Tolerance of Commercial Peach Cultivars to Brown Rot Caused by Monilinia laxa Modulated by its Antioxidant Content?

Abstract: Brown rot, caused by Monilinia spp., provokes pre- and post-harvest damage in peach (Prunus persica (L.) Batsch), which causes an economic impact in the industry. With a view to breeding for increased tolerance to this disease, a screening test based upon artificial fruit inoculation was validated on several parental lines of a peach breeding program during the two-period harvest. In addition, cultivars with different total phenolic contents were included in the two-year study. All physicochemical fruit traits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Also, other researchers have shown a significantly higher content of total phenols, total flavonoids and tannins in asymptomatic leaves of persimmom (Dyospiros kaki) cultivars affected by Plurivorosphaerella nawae fungus, compared with symptomatic leaves (Hassan et al, 2020). However, Obi et al, 2020 supported that besides the phenolics, neither ascorbate nor glutathione or carotenoids have ever been considered in conferring tolerance to brown rot in peach.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Also, other researchers have shown a significantly higher content of total phenols, total flavonoids and tannins in asymptomatic leaves of persimmom (Dyospiros kaki) cultivars affected by Plurivorosphaerella nawae fungus, compared with symptomatic leaves (Hassan et al, 2020). However, Obi et al, 2020 supported that besides the phenolics, neither ascorbate nor glutathione or carotenoids have ever been considered in conferring tolerance to brown rot in peach.…”
Section: Resultsmentioning
confidence: 96%
“…Numerous scientific reports suggest involvement of phenolic compounds and assimilation pigments in plant defense against different pathogens (Ivascu et al, 2002;Arun et al, 2010;Petrisor et al, 2012;Rasoulnia et al, 2018;Almatwari et al, 2020;Del Cueto et al, 2021). Previous work on resistance mechanisms to apple scab Venturia inaequalis (Cke.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlorogenic acid, the most abundant representative, was in boundary tissue of infected apple peel up to 6.6-fold higher (INF_CUR_C) compared to healthy tissue. Increasing contents of chlorogenic acid and its derivatives have already been associated with a reduction in the susceptibility of fruit to brown rot infections [49][50][51][52]. Villarino et al [50] reported that chlorogenic acid concentrations, similar to those in peach fruit, does not inhibit spore germination or mycelial growth of fungus M. laxa in culture but inhibits the production of melanin-like pigments in the mycelia of M. laxa in culture (42% melanin reduction).…”
Section: Discussionmentioning
confidence: 99%
“…Manuring can influence disease incidence, and applications of potassium have brought about a reduction in disease incidence on apricots [P. armeniaca] (Yin et al, 2017). High doses of nitrogen fertilizer are positively correlated with infection by M. fructigena (Obi et al, 2020).…”
Section: Tebuconazolementioning
confidence: 99%